Repulsive particle interactions enable selective information processing at cellular interfaces - Elliott, Jenna; Shah, Hiral; Belousov, Roman; Dey, Gautam; Erzberger, Anna (Physical review letters, 2025)
Living systems relay information across membrane interfaces to coordinate compartment functions. We identify a physical mechanism for selective information transmission that arises from the sigmoidal response of surface-bound particle densities to spatial features in adjacent external structures through a nonuniform binding energy. This mechanism implements a form of spatial thresholding, enabling the binary classification of external cues. Expansion microscopy measurements of nuclear pore complex distributions in S. arctica show signatures of such physical thresholding.
Gesehen am 25.02.2026